KARAKTERISTIK TEGANGAN TEMBUS PITA ISOLASI - , USMAN NAWAWI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Insulation system is one of important issue in order to maintain electrical distribution continuity. Insulation system is higly needed in transmition system, distribution system, and household area.In household area commonley used material like PVC. However,If something problem in insulation system, it must taken care as soon as posssible. Beetwen this situation, insulation for maintenance in household area must be efficient, effective, and cheap, usually they used unexperience material likeinsulation tape. Considering of its effectiveness and cost, insulation tape are a good stuff. However, there is some question about their security and ability to maintain electrical system from insulation failure. This matter need more researches because insulation tape is not foundin insulation book.This experiment was conducted in order to know tape insulation voltage breakdowncharacteristic. Hopefully, in the future this work can guide ordinary people how to use insulation tape in their electrical insulation problem.The resume of this experiment gave an information that breakdown voltage of PVC tape insulation at first folded withaout any addition is 5 KV, so we can assume that tape is good enaugh to be used in electrical insulation on household area.